Cell proliferation activity delineated by molecular docking of four new compounds isolated from the aerial parts of Suaeda monoica Forssk. ex. J.F. Gmel - Nasir A. Siddiqui; Ramzi A. Mothana; Mansour S. Al-Said; Mohammad K. Parvez; Perwez Alam; M. Tabish Rehman; Mohd. Ali; Mohamed F. Alajmi; Mohammed S. Al-Dosari; Adnan J. Al-Rehaily; Fahd A. Nasr; Jamal M. Khalid (Elsevier, 2020)
Using different chromatographic methods, four new compounds were isolated from the aerial parts of Suaeda monoica (Chenopodiaceae) along with 2-hydroxy-1-naphthoic acid (SCM-3). The structures of the new compounds were established as 6'-hydroxy-10'-geranilanyl naphtha-1-oate (SMC-1), 4,4,8β,10β-Tetramethyl-9β-isobutanyl decalin-13-ol-13-O-β-D-xylopyranoside (SCM-2), 6'-(2-hydroxynaphthalen-3-yl) hexanoic acid (SCM-4) and 1'-(2-Methoxy-3-naphthyl)-4'-(2''-methylbenzoyl)-n-butane (SMC-5) by IR, EIMS and NMR (1 & 2D) analyses. All compounds (50 μg/mL) were tested for cell proliferative potential on cultured human liver cell HepG2 cells by MTT assay. The results revealed a marked cell proliferative potential of all compounds (1.42-1.48 fold) as compared to untreated control. The results of molecular docking and binding with specific proteins such as PTEN (Phosphatase and Tensin homolog) and p53 also justify the cell proliferative potential of the isolated compounds. Glide program with Schrodinger suit 2018 was used to evaluate the binding between SMC compounds and proteins (PTEN and p53). The binding affinity of all compounds was in order of 104-105 M−1 towards both PTEN and p53. All the SMC compounds have been found to bind at the active site of PTEN, thereby may prevent the binding of phosphatidylinositiol 3,4,5-triphosphate (PI3P). In the locked position, PTEN would not be able to hydrolyze PI3P and hence the PI3P regulated signaling pathway remains active. Similarly, SMC molecules were found to interact with the amino acid residues (Ser99, Thr170, Gly199, and Asp224) which are critically involved in the formation of tetrameric p53. The blockage of p53 to attain its active conformation thus may prevent the recruitment of p53 on DNA and hence may promote cell proliferation. Keywords: Suaeda monoica, Cell-proliferation, Molecular docking, β-Naphthol, Caproic acid, Chenopodiaceae, HepG2 cells